The Effect of Using Interactive E-activities on Motivation towards Learning and Academic Achievement of Tenth-Grade Female Students in the Information Technology and Computer course - Al-Shamhani, Manal Mohammed; Al Massad, Ahmed Zaid (Journal of Curriculum and Teaching Methodology, 2024)
This study aimed at identifying the effect of using electronic interactive activities when teaching the course of Computer and Information Technology on motivation towards learning and development of acquisition with the first female high school students. To achieve this objective, a quasi-experimental approach was used. Two research tools were designed by the researcher, i.e., a test and a measurement for motivation towards learning. The sample of the study was composed of (60) female students from Fatima Bent Mohammed High School situated in the National Guard. Two classes, (30) students each, of the first female high school who studied the course of Computer and Information Technology were selected randomly to form the experimental and control groups. The findings of the study revealed that: the female students of the experimental group who were taught the electronic interactive activities scored higher marks in the test than those of the control group who were taught in the traditional method; the female students of the experimental group who were taught the electronic interactive activities scored higher marks in some of the dimensions of the test (i.e., recall, analysis, and application) than those of the control group who were taught in the traditional method.A number of recommendations were introduced, notably: training both female students and teachers, from anywhere and at any time, on using electronic interactive activities and learning ways for developing them; and including and designing electronic interactive activities in all curricula, the curriculum of computer, in particular.
Keywords: Electronic Interactive Activities; Motivation; Learning Acquisition; Computer Course; High School Stage